2020
DOI: 10.1038/s41598-020-77555-4
|View full text |Cite
|
Sign up to set email alerts
|

ELISA detection of SARS-CoV-2 antibodies in saliva

Abstract: To facilitate containment of the COVID-19 pandemic currently active in the United States and across the world, options for easy, non-invasive antibody testing are required. Here we have adapted a commercially available, serum-based enzyme-linked immunosorbent assay (ELISA) for use with saliva samples, achieving 84.2% sensitivity and 100% specificity in a set of 149 clinical samples. This strategy will enable widespread, affordable testing for patients who experienced this disease, whilst minimizing exposure ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 18 publications
5
76
1
1
Order By: Relevance
“…A recent study suggested that salivary SARS-CoV-2 viral load can serve as a dynamic correlate of COVID-19 severity and mortality(24). The utility of SARS-CoV-2 RNA detection in saliva has emerged in parallel with proofs-of-principle to detect SARS-CoV-2-specific antibody responses in saliva, which could serve as a surrogate of SARS-CoV-2 serological tests (10, 12, 17, 21). SARS-CoV-2-specific IgG in saliva reflects the blood-derived transudate in the oral cavity; by contrast, SARS-CoV-2-specific IgA in saliva may represent a localized mucosal IgA response to infection (2, 22, 27).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that salivary SARS-CoV-2 viral load can serve as a dynamic correlate of COVID-19 severity and mortality(24). The utility of SARS-CoV-2 RNA detection in saliva has emerged in parallel with proofs-of-principle to detect SARS-CoV-2-specific antibody responses in saliva, which could serve as a surrogate of SARS-CoV-2 serological tests (10, 12, 17, 21). SARS-CoV-2-specific IgG in saliva reflects the blood-derived transudate in the oral cavity; by contrast, SARS-CoV-2-specific IgA in saliva may represent a localized mucosal IgA response to infection (2, 22, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to resolve this shortage and support state-led diagnostic efforts, many research laboratories have repurposed their expertise, skilled labor and equipment by developing and assembling in-house testing kits, among other efforts [4][5][6][7] . SARS-CoV-2 serological tests employ enzyme-linked immunosorbent assay (ELISA) 8,9 , immunofluorescence 10 and lateral flow techniques to detect antibodies directed against the nucleocapsid (N) and/or Spike (S) proteins of the viral proteome 11 .…”
Section: Introductionmentioning
confidence: 99%
“…From positive participants, serum and oral fluid was collected at least 21 days after the date of reported symptom onset to ensure adequate time for antibody seroconversion (2). We tested participant serum specimens on the EuroImmun Anti-SARS-CoV-2 (IgG) ELISA (12) to determine whether the participants were expressing antibodies against the virus using previously described methods (9) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The OACD, when used with the Anti-SARS-CoV-2 total antibody ELISA kit developed by OraSure® Technologies, has achieved sensitivity and specificity which are equivalent to commercially available serum-based ELISAs(9). This represents a unique and highly successful advancement in antibody detection technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation